2016
DOI: 10.1681/asn.2015030302
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveals a Key Role for Fumarate in Mediating the Effects of NADPH Oxidase 4 in Diabetic Kidney Disease

Abstract: The NADPH oxidase (NOX) isoform NOX4 has been linked with diabetic kidney disease (DKD). However, a mechanistic understanding of the downstream effects of NOX4 remains to be established. We report that podocyte-specific induction of NOX4 in vivo was sufficient to recapitulate the characteristic glomerular changes noted with DKD, including glomerular hypertrophy, mesangial matrix accumulation, glomerular basement membrane thickening, albuminuria, and podocyte dropout. Intervention with a NOX1/NOX4 inhibitor red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
161
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 47 publications
7
161
0
8
Order By: Relevance
“…Succinate, a ligand of the G protein-coupled receptor GPR91, can activate the renin-angiotensin system (39)(40)(41), and the activation of angiotensin II may result in NADPH oxidase 4-generated (Nox4-generated) mitochondrial oxidative damage (42,43), leading to a feed-forward mechanism that promotes kidney injury in diabetes. Fumarate, which also accumulates in the diabetic kidney and urine of a type 1 model of DKD, is a potent inducer of HIF-1α and TGF-β, both of which could contribute to kidney disease pathology (44). Second, metabolic intermediates may alter metabolic enzyme activity through the generation of post-translational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Succinate, a ligand of the G protein-coupled receptor GPR91, can activate the renin-angiotensin system (39)(40)(41), and the activation of angiotensin II may result in NADPH oxidase 4-generated (Nox4-generated) mitochondrial oxidative damage (42,43), leading to a feed-forward mechanism that promotes kidney injury in diabetes. Fumarate, which also accumulates in the diabetic kidney and urine of a type 1 model of DKD, is a potent inducer of HIF-1α and TGF-β, both of which could contribute to kidney disease pathology (44). Second, metabolic intermediates may alter metabolic enzyme activity through the generation of post-translational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections (5 μm) were stained with periodic acid-Schiff (PAS) and imaged by light microscopy. Immunofluorescent staining of WT1 in the cryosections was carried out as described (48). Briefly, sections were incubated overnight at 4°C with antibodies against WT1, washed with PBS, and incubated for 1 hour at room temperature with Alexa Fluor-conjugated secondary antibodies and visualized by a BIOREVO BZ-9000 fluorescence microscope (Keyence).…”
Section: Gene Expression Analysis Of Human Renal Biopsiesmentioning
confidence: 99%
“…BUN was assessed with a colorimetric assay (DiaSys) and calculated as mg/dl. Urine metabolomics was performed as per our recent publications (3,48).…”
Section: Gene Expression Analysis Of Human Renal Biopsiesmentioning
confidence: 99%
“…In this issue of JASN, You et al 15 make a valuable contribution to the literature, expanding the role for NOX4 in diabetic kidney disease to include the regulation of intermediary metabolism. More specifically, You et al 15 show that NOX4 modulates levels of the tricarboxylic acid (TCA) cycle intermediate fumarate through its effects on fumarate hydratase (FH) expression (FH catalyzes the hydration of fumarate to malate).…”
mentioning
confidence: 99%
“…More specifically, You et al 15 show that NOX4 modulates levels of the tricarboxylic acid (TCA) cycle intermediate fumarate through its effects on fumarate hydratase (FH) expression (FH catalyzes the hydration of fumarate to malate). Using a metabolomics screen, You et al 15 found dramatic increases in several TCA cycle intermediates in the urine of F1 Akita mice, a model of type 1 diabetic kidney disease, compared with F1 controls. Only fumarate levels, however, fell in a dose-dependent manner after NOX4 inhibition with GKT137831.…”
mentioning
confidence: 99%